2008
DOI: 10.1074/jbc.m802585200
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Directly Regulates Skeletal Muscle Fibrosis

Abstract: Skeletal muscle fibrosis is a major pathological hallmark of chronic myopathies in which myofibers are replaced by progressive deposition of collagen and other extracellular matrix proteins produced by muscle fibroblasts. Recent studies have shown that in the absence of the endogenous muscle growth regulator myostatin, regeneration of muscle is enhanced, and muscle fibrosis is correspondingly reduced. We now demonstrate that myostatin not only regulates the growth of myocytes but also directly regulates muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
187
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 41 publications
12
187
1
Order By: Relevance
“…However, other signaling pathways including Smad2 are also shown to be involved in myostatin signaling [9,13,[39][40][41][42]. In this study, higher myostatin level was shown to be, in part, responsible for the muscle atrophy in Smad3-null mice.…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Inmentioning
confidence: 59%
See 1 more Smart Citation
“…However, other signaling pathways including Smad2 are also shown to be involved in myostatin signaling [9,13,[39][40][41][42]. In this study, higher myostatin level was shown to be, in part, responsible for the muscle atrophy in Smad3-null mice.…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Inmentioning
confidence: 59%
“…Mechanistically, the Smad2/3 pathway plays a significant role in myostatin and TGF-β signaling and inhibition of myogenesis [10,11]. Specifically, Smad3 is required for the inhibition of myoblast differentiation by myostatin [12] and for the activation of fibroblast proliferation by myostatin [13]. The Smad3-dependent pathway begins when activated myostatin receptors (activin type IIB receptor/ALK5) form heterotetrameric complexes, which then recruit, phosphorylate and activate the receptor-regulated SMADS (R-Smads).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In vitro studies localize MSTN and ActRIIB directly on fibroblasts, supporting the idea that MSTN is a profibrotic factor that interacts directly with fibroblasts to mediate its effects. 58 In vivo, MSTN-coated beads implanted into skeletal muscle increased fibrotic tissue, and this effect was inhibited when the endogenous MSTN inhibitor follistatin was also present on the beads. 58 Diaphragmatic fibrosis was reduced by 44% in Mstn Ϫ/Ϫ mdx mice at 6 months of age, compared with Mstn ϩ/ϩ mdx mice, but was still elevated compared with the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…In the myogenesis program, myogenic differentiation 1 (MYOD1) and myogenic factor 5 (MYF5) are important for myogenic differentiation of satellite cells, myoblast commitment, and induction of myogenin (MYOG, which helps control the formation of myotubes and normal muscle development) 20 . On the other hand, myostatin (MSTN), which is secreted by muscle, inhibits myogenesis 21 and muscle hypertrophy [22][23][24] (via regulation of mammalian target of rapamycin [MTOR]) but promotes fibrosis 25,26 and adipogenesis 21 . An animal model of rotator cuff injury has also shown that MTOR modulates fatty infiltration 27 , and it regulates fibrosis [28][29][30] .…”
mentioning
confidence: 99%